From Love to Family Happiness: a Theoretical Model for Javanese Family* - Andayani, Budi; Ancok, Djamaludin; Wulan, Ratna (European Journal of Social Science Education and Research, 2020)
This study empirically tested a model involving Marital Commitment, Positive Communication Style, and Family Process as mediators that support the influence of Love to Family Happiness. A total of 201 families consisting of father, mother, and one adolescent representing all the children in the family, participated in this study. Family participants have the characteristics of average numbers of children of 2-3, with spouses married for more than 10 years, with senior high school or college education level, were intact families, spouses were not in the process to divorce, and the whole family lived together. Children participants were junior or senior high school students in Yogyakarta. Participants were asked to fill in several related scales. Family Happiness Scale, Family Process Scale and Scale of Positive Communication Style responded by the three groups of participants, namely Father, Mother, and Children. Love Scale, and Marital Commitment Scale were responded by husbands and wives. To test the model Structural Equation Modeling was applied using LISREL 8.80 program. The result shows the theoretical mediating model of Marital Commitment, Positive Communication Style, and Family Process strengthen the influence of Love on Family Happiness fit with the data. This suggests that (1) marital commitment and positive communication styles are important personal characteristics for the realization of family happiness, or in other words, love is insufficient for the realization of family happiness; (2) family process has a strong role as a mediator between marital commitment and positive communication style together, on family happiness. Further concluded theoretically that the essence of the realization of family happiness is rukun that includes closeness, bonding, and caring, which manifest in cooperation among family members.